2021
DOI: 10.1021/acsomega.1c01467
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Zn-Doped Bi2O3 Nanoparticles and Their Selective Cytotoxicity toward Cancer Cells

Abstract: Bismuth (III) oxide nanoparticles (Bi 2 O 3 NPs) have shown great potential for biomedical applications because of their tunable physicochemical properties. In this work, pure and Zn-doped (1 and 3 mol %) Bi 2 O 3 NPs were synthesized by a facile chemical route and their cytotoxicity was examined in cancer cells and normal cells. The X-ray diffraction results show that the tetragonal phase of β-Bi 2 O 3 remains unchanged after Zn-doping. Transmission electron microscopy and scanning electron microscopy images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Moreover, Zn-doped Bi 2 O 3 NPs exhibited significant cytotoxicity against human lung (A549) and liver (HepG2) cancer cells, and the cytotoxicity intensity increased with increasing concentration of Zn-doping, indicating that Zn-doped Bi 2 O 3 NPs induce cytotoxicity in both types of cancer cells through the generation of ROS and caspase-3 activation. 41 In this study, we detected the inhibitory effect of ZnO NPs on the proliferation of human AML cells, and the results showed that ZnO NPs could significantly inhibit cell proliferation and facilitate the apoptosis of human monocytic cell line THP-1 cells. Our previous studies have found that ZnO NPs can exhibit apparent cytotoxic effect on leukemia cells, 42 rat retinal ganglion cells, 43 and mouse photoreceptor cells at high concentrations, 44 which were consistent with the present findings.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, Zn-doped Bi 2 O 3 NPs exhibited significant cytotoxicity against human lung (A549) and liver (HepG2) cancer cells, and the cytotoxicity intensity increased with increasing concentration of Zn-doping, indicating that Zn-doped Bi 2 O 3 NPs induce cytotoxicity in both types of cancer cells through the generation of ROS and caspase-3 activation. 41 In this study, we detected the inhibitory effect of ZnO NPs on the proliferation of human AML cells, and the results showed that ZnO NPs could significantly inhibit cell proliferation and facilitate the apoptosis of human monocytic cell line THP-1 cells. Our previous studies have found that ZnO NPs can exhibit apparent cytotoxic effect on leukemia cells, 42 rat retinal ganglion cells, 43 and mouse photoreceptor cells at high concentrations, 44 which were consistent with the present findings.…”
Section: Discussionmentioning
confidence: 86%
“…Ahamed et al 40 found that bismuth oxide nanoparticles (Bi 2 O 3 NPs) induced cytotoxicity in human breast cancer (MCF‐7) cells by modulating the redox homeostasis via Bax/Bcl‐2 pathway. Moreover, Zn‐doped Bi 2 O 3 NPs exhibited significant cytotoxicity against human lung (A549) and liver (HepG2) cancer cells, and the cytotoxicity intensity increased with increasing concentration of Zn‐doping, indicating that Zn‐doped Bi 2 O 3 NPs induce cytotoxicity in both types of cancer cells through the generation of ROS and caspase‐3 activation 41 …”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress-mediated anticancer activity of other nanoscale materials has also been proposed [ 50 , 59 ]. For example, our recent studies indicated that ZnO/RGO NCs and Zn-doped Bi 2 O 3 NPs displayed anticancer activity through ROS generation [ 32 , 60 , 61 ]. The possible mechanism of anticancer performance in Ag/RGO NCs is depicted in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to SPIONs, MAGNCs were relatively stable in the water phase due to gelatin with a large portion of hydrophilic amino acids (lysine, serine, arginine, aspartic acid, and glutamic acid) [ 21 ]. According to several reports, the colloidal particle from the green synthesis using nature biomolecules such as fruits, vegetables, or plants provided the various nanoparticles with highly effective biofunctional performance and better cytocompatibility [ 22 , 23 , 24 , 25 ]; therefore, MAGNC synthesized from the AG would not affect the native morphology of chondrocytes. In addition, the viability of MAGNC-treated chondrocytes is an essential factor for cell therapy in cartilage repair; therefore, various concentrations of MAGNCs were incubated with chondrocytes for 1, 3, and 7 days to evaluate cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%